Impact of virtual influencers' attributes on purchase intention - Francisco, Catarina Maria Garcia (2024)
The interest in virtual influencer marketing has significantly increased among academics, entrepreneurs, investors, and consumers. This concept is associated with artificial intelligence, aiming to equip machines with the ability to replicate human-like skills (creativity, reasoning, etc.). Virtual influencers (VIs) are one of the technologies supporting this new era of artificial intelligence. Linked to social media platforms, VIs emerged with the aim of revolutionizing global marketing strategies. For example, Lil Miquela (@lilmiquela on Instagram) has over 2 million followers on Instagram and has collaborated with various brands such as Calvin Klein, BMW, Balmain, Chanel, and Apple. VIs offer unique features, such as brands' control over the content shared on social media, cost reduction, and independence. However, they continue to evoke controversy and uncertainty about their utility. This study adopts a marketing perspective that explores the impact of VIs attributes on social media users' purchase intention. Based on previous models and studies, and adapting the Human Brand Theory to the virtual world, a conceptual framework was developed to examine inspiration, visual aesthetics, enjoyability, similarity, and expertise of VIs. A quantitative approach was adopted through an online survey targeting social media users.